2020
DOI: 10.1002/nau.24342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of female urinary incontinence in the developing world: A systematic review and meta‐analysis—A Report from the Developing World Committee of the International Continence Society and Iranian Research Center for Evidence Based Medicine

Abstract: Aims: The prevalence of urinary incontinence (UI) in the developing world varies widely. Factors influencing prevalence rates are a key area of interest, and knowledge of these would provide appropriate planning for preventive primary and secondary health care programs. The objective of this report was to synthesize the best available evidence to determine UI prevalence rates in adult women in a population setting.Methods: A comprehensive search strategy was employed to find published and unpublished studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 71 publications
1
50
3
5
Order By: Relevance
“…The prevalence of urinary incontinence in population of adult women is 25,7% [1]. Stress urinary incontinence (SUI) occurs when an increase in intra-abdominal pressure, caused for example by coughing or heavy physical work, is accompanied by the involuntary passing of urine [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of urinary incontinence in population of adult women is 25,7% [1]. Stress urinary incontinence (SUI) occurs when an increase in intra-abdominal pressure, caused for example by coughing or heavy physical work, is accompanied by the involuntary passing of urine [2].…”
Section: Introductionmentioning
confidence: 99%
“…Stress urinary incontinence (SUI) occurs when an increase in intra-abdominal pressure, caused for example by coughing or heavy physical work, is accompanied by the involuntary passing of urine [2]. The prevalence of SUI stress urinary incontinence among adult women is 12,6%, and the most important risk factors are obstetric history [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted in Zambia found a low level of disclosure by adults that they were experiencing incontinence symptoms (that is, self-wetting), with a reluctance to disclose attributed to a lack of awareness that incontinence is a medical condition, and/or the stigma associated with the condition (Rosato-Scott and Barrington, 2018). Interviews with adults and their caregivers revealed this reluctance to disclose rather than an absence of UI, and this is supported by systematic reviews looking at the prevalence of adults experiencing UI in LMICs which find rates in line with global estimates (Walker and Gunasekera, 2011;Rosato-Scott and Barrington, 2018;Mostafaei et al, 2020).…”
Section: [A]discussionmentioning
confidence: 81%
“…3 However, in developing countries, the prevalence is increased to 58%. 4 The global annual costs of the women's UI are more than the expenses of breast, ovals, cervix and uterus cancers combined, [5][6][7] which highlights the importance of UI among females. Besides the financial issues, the UI causes depression, shame and nervousness in patients and decreases the self-efficiency, effective attendance in the society and the quality of life.…”
Section: Introductionmentioning
confidence: 99%